FOREIGN INVESTMENTS IN PRIORITY SECTOR THE ECONOMY OF KAZAKHSTAN - Petr, Hájek, (Farabi Journal of Social Sciences, 2019)
Abstract. The inflow of foreign direct investment in Kazakhstan is carried out through the establishment of joint ventures, subsidiaries, privatization of state-owned enterprises with foreign capital, transfer of large industrial enterprises to the management of foreign firms and investment in the banking sector. The article analyzes the inflow of foreign direct investment in the context from 2014 to 2018, in the priority sectors of the economy of the Republic of Kazakhstan, which are the mining industry, processing industry, professional scientific and technical activities and innovative development. The paper deals with the issues of investment in priority sectors of the economy of Kazakhstan. The methodological basis of the research was analytical and statistical methods, dialectical method of cognition and observation. The works of well-known authors of economists were studied and considered. According to the research of the analytical review, by 2022 the inflow of foreign direct investment should grow by 26% compared to the data of 2016, and the ratio of FDI to GDP should be at the level of 19%, while at the moment this figure is 16.5%. Given the investment restructuring and the direction of investment in the service segment of the economy, by 2022 the volume of foreign investment in fixed assets of the non-commodity sector of the economy should increase to 50%, also compared to 2016. The bulk of foreign investment continues to be directed to areas that do not require large-scale investments and are characterized by rapid payback. Thus, drawing a conclusion on the study of trends in the functioning, outflow and inflow of foreign direct investment in the priority sectors of the economy of the Republic of Kazakhstan, in the sectoral structure of investments, the main share is the mining industry, and the oil and gas industry is still in one of the first places in terms of attracted investments. Industries such as construction and manufacturing receive the least amount of foreign investment. The article has scientific value and novelty of research.